2021
DOI: 10.3390/plants10010183
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Ficus Crocata Extract on Cervical Cancer Cells and Protective Effect against Hydrogen Peroxide-Induced Oxidative Stress in HaCaT Non-Tumor Cells

Abstract: Oxidative stress causes several chronic diseases including cancer. Some chemotherapeutic agents are not selective against tumor cells, causing oxidative stress in non-tumor cells. This study aimed to evaluate the cytotoxic effect of acetone extract of Ficus crocata(Miq.) Mart. ex Miq. (F. crocata) leaves (Ace-EFc) on cervical cancer cells, as well as its protective effect on hydrogen peroxide (H2O2)-induced lipoperoxidation and cytotoxicity in non-tumor HaCaT cells. Antioxidant activity was determined using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Two internationally well-known fibroblast (L929) and epithelial (HaCaT) cell lines were used for the in vitro analysis, following DIN EN ISO 10993-5 standards. Furthermore, they represent typical starting cell lines for future investigations in the field of external wound treatment ( Rajan et al, 2020 ; Ribeiro et al, 2020 ; De la Cruz-Concepción et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two internationally well-known fibroblast (L929) and epithelial (HaCaT) cell lines were used for the in vitro analysis, following DIN EN ISO 10993-5 standards. Furthermore, they represent typical starting cell lines for future investigations in the field of external wound treatment ( Rajan et al, 2020 ; Ribeiro et al, 2020 ; De la Cruz-Concepción et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hot water is a good solvent strategy, as it has improved the extraction of antioxidant compounds in roots from F. dubia (Suttisansanee et al, 2021). The acetone extract from the leaves of F. crocata showed antioxidant activity (IC50, 107.05 ± 2.61 µg/mL by DPPH˙ and 1.47 ± 1.21 µg/mL by ABTS+˙) higher than ascorbic acid (IC50, 118.82 ± 2.48 µg/mL by DPPH˙ and 2.22 ± 0.80 µg/mL by ABTS+˙) (Cruz-Concepción et al, 2021).…”
Section: Antioxidant Activitymentioning
confidence: 96%
“…The presence of terpenes was also identified, among them the lupeol triterpenes (Cruz-Concepción et al, 2021;El-Beltagi et al, 2019;Knothe et al, 2019;Mbougnia et al, 2021;Sánchez-Valdeolívar et al, 2020), squalene (Cruz-Concepción et al, 2021;Knothe et al, 2019;Sánchez-Valdeolívar et al, 2020;Tian et al, 2020), lanosterol (El-Beltagi et al, 2019), diterpene phytol (Cruz-Concepción et al, 2021;El-Beltagi et al, 2019;Lawal et al, 2016), monoterpene linalool, and the sesquiterpene β-caryophyllene (Lawal et al, 2016;Soltana et al, 2017;Tian et al, 2020), mainly identified in leaves (F.…”
Section: Terpenes Steroids and Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations